Background Paper - Durie, E T (Victoria University of Wellington Law Review, 1995)
The Treaty of Waitangi Act 1975 constitutes the Waitangi Tribunal comprised of the Chief Judge of the Maori Land Court as chairperson and up to 16 additional members appointed by the Crown for terms not exceeding three years.